2018
DOI: 10.1016/j.oooo.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the expression of DNA damage response-related molecules in potentially preneoplastic oral epithelial lesions

Abstract: DDR markers' expression is variable in PPOELs, showing a tendency to increase along with dysplasia. Activated DDR mechanisms may play an important protective role at early stages of oral carcinogenesis, but probably suffer progressive deregulation, eventually failing to suppress malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…The direct evaluation of the DNA sensing-signalling-damage repair cascade in OED has not been previously reported, although there is recent evidence that individuals with reduced, systemic, double strand break repair capacity are more prone develop to head and neck cancer (38). It has been suggested that activation of DNA damage response might be protective in the early stages of oral carcinogenesis, but progressive deregulation over time could eventually result in the failure to suppress malignant transformation (41). The results of the current study indicate that additional evaluation of these pathways is worthwhile to understand their capability to predict malignant transformation in OED at the initial diagnostic biopsy, especially as time to transformation may be as long as 7 years (1,3).…”
Section: Discussionmentioning
confidence: 99%
“…The direct evaluation of the DNA sensing-signalling-damage repair cascade in OED has not been previously reported, although there is recent evidence that individuals with reduced, systemic, double strand break repair capacity are more prone develop to head and neck cancer (38). It has been suggested that activation of DNA damage response might be protective in the early stages of oral carcinogenesis, but progressive deregulation over time could eventually result in the failure to suppress malignant transformation (41). The results of the current study indicate that additional evaluation of these pathways is worthwhile to understand their capability to predict malignant transformation in OED at the initial diagnostic biopsy, especially as time to transformation may be as long as 7 years (1,3).…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type p53 protein is expressed in < 5% of basal cells in normal epithelium [40]. Its expression is increased in OED although the degree of expression varied in studies by different studies [40][41][42]. However, if there is continuous positivity within > 90% of basal cell nuclei and in suprabasal nuclei, this is very strongly associated with the dysplastic phenotype; it is also strongly expressed in SCC.…”
Section: Keratosis Of Uncertain Significance (Kus)mentioning
confidence: 99%
“…The direct evaluation of the DNA sensing-signalling-damage repair cascade in OED has not been previously reported, although there is recent evidence that individuals with reduced, systemic, double strand break repair capacity are more prone develop to head and neck cancer (38). It has been suggested that activation of DNA damage response might be protective in the early stages of oral carcinogenesis, but progressive deregulation over time could eventually result in the failure to suppress malignant transformation (41). The results of the current study indicate that additional evaluation of these pathways is worthwhile to understand their capability to predict malignant transformation in OED at the initial diagnostic biopsy, especially as time to transformation may be as long as 7 years (1, 3).…”
Section: Discussionmentioning
confidence: 99%